Collaborative Learning Techniques in Python Programming: A Case Study with CSE Students at Anurag University - Rathna Sekhar, P.; Goud, Swapna (Journal of Engineering Education Transformations, 2025)
Today’s education system requires new, interactive methods to keep students interested and help them learn better. This paper looks at various Teaching-Learning Process (TLP) methods used to teach Python programming to B.Tech CSE students. The methods include Chalk & Talk with PowerPoint, Think Pair Share, Open-ended problems in Laboratories, Quality Circles, Concept Mapping, Web-based Learning, Moodle, Mock Interviews, and Think Aloud Pair Problem Solving. These methods were included in the curriculum to make the classroom more engaging and participative. The aim was to change traditional teaching into an interactive experience, encouraging students to actively participate, collaborate, and use their knowledge in real-life situations. Each TLP method covered different learning aspects, from understanding theory to solving practical problems. Using these methods in teaching Python showed great improvements in student involvement, understanding, and retention. These methods were used on one of the batches of CSE department, and results show a significant improvement in final results. This paper details each method, its classroom use, and the observed outcomes, offering recommendations for educators to improve teaching practices in technical education.